Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top


Let $y'(t)=f(t,y(t))$ and $y(0)=y_0$

The backward euler method together with the center rule is given by:

$y(t_k)=hk$ where $h\in (0,\frac{1}{K})$ is the step size.

Recursion: $y_k=y_{k-1}+hf(t_{k-1}+\frac{h}{2},\mu_{k-1})$ where $\mu_{k-1}=y_{k-1}+\frac{h}{2}f(t_{k-1},y_{k-1})$

Question: I want to use the method now for $y'(t)=\lambda y(t), t>0$ and $y(0)=y_0$ to evaluate for which $\lambda$ the sequence $(y_k)_{k\in\mathbb N}$ converges to $0$

I tried to evaluate some $y_k$ but I couldn' tsee anything.

share|cite|improve this question
up vote 3 down vote accepted

This doesn't look like backward Euler method to me; it looks more like a 2nd order Runge-Kutta scheme. A backward Euler method would be $y_{k+1}=y_k+hf(t_{k+1},y_{k+1})$; see here for details.

Assuming you actually want to use the recursion which you have given, first note that $f(t,y)=\lambda y$, so that $$\mu_{k-1}=y_{k-1}+\frac{h}{2}\lambda y_{k-1}=(1+h\lambda/2)y_{k-1}.$$

Then, $$y_{k}=y_{k-1}+h\lambda\mu_{k-1}=y_{k-1}+h\lambda(1+h\lambda/2)y_{k-1}=\frac{1}{2}\left(2+2h\lambda+h^2\lambda^2\right)y_{k-1}.$$

You should now be able to determine which choices of $\lambda$ ensures $\lim\limits_{k\rightarrow\infty}y_k=0$.

Added You can also solve the problem analytically, giving $y(t)=Ce^{\lambda t}$, which approaches $0$ as $t\rightarrow\infty$ when $\operatorname{Re}(\lambda)<0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.